STRATEGY FOR DEVELOPING THE HALAL COSMETIC INDUSTRY IN INDONESIA TO IMPROVE COMPETITIVENESS IN THE GLOBAL MARKET - Mohammad Abdurrahman (Nurul Jadid University, 2025)
The halal cosmetics industry has experienced significant growth along with the increasing awareness and demand of Muslim consumers for sharia-compliant products. The development of the halal cosmetics industry in Indonesia faces unique challenges and opportunities. This study examines strategies that can be implemented to optimize the development of this industry. Some of the main strategies analyzed include improving product quality and innovation, halal certification, effective marketing, adequate infrastructure and collaboration with various stakeholders. The results of the study show that by implementing these strategies, the halal cosmetics industry in Indonesia can increase its competitiveness in the global market and meet the growing needs of Muslim consumers. This study is a descriptive qualitative study that aims to provide a detailed description of the development of the halal cosmetics industry in Indonesia, identify existing challenges and opportunities, and formulate effective strategies to advance this sector to the international level. By implementing these strategies, the Indonesian halal cosmetics industry can increase its competitiveness in the global market and meet the growing needs of Muslim consumers